Centralised Acquisition of Periodicals (CAP) Project of INSDOC - A Participant’s View - Karnad, Suman; Ragavan, M. C. (Journal of Information and Knowledge, 1982)
A before and after study of the acquisition of periodicals through the Centralised Acquisition of Periodicals project of INSDOC is described. Earlier, the periodicals were observed by direct subscription to the publisher. Since the introduction of the CAP, the orders for periodicals are placed on INSDOC. The details of work-flow, advantages and disadvantages between the direct subscription procedure and CAP are evaluated. Some suggestions for improvement in the CAP are made.